Use of Prezi Software in Making Presentations at Elementary Schools for the Independent Curriculum - Prijambodo, Raden Firman Nurbudi; Wang, Yuanyuan; Zou, Guijiao; Sujatmiko, Wandi; Masnunah, Masnunah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Presentations in the form of Multimedia Presentation online can generate interest in students and help them understand the content to be communicated effectively, where the prezi program is a program that can create presentations in a modern style. and can be combined with programs in the management of many types of images and sounds, creating works that can be applied in various ways. The research objectives are 1) to find out whether the use of prezi software in making presentations is effective in elementary schools for the independent curriculum. 2) the effect of prezi software on student learning outcomes. 3) Obstacles in using prezi software. This research method uses quantitative methods, data obtained from google questionnaires from elementary school students. The results showed that prezi software was very influential on presentations in elementary schools as evidenced by student learning motivation. The conclusion of this research is that prezi software can be applied in presentations as evidenced by the results of research that the learning outcomes of elementary school students using prezi software increased by 80%.